2014
DOI: 10.1016/j.bbrc.2014.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells from osteoporotic patients reveal reduced migration and invasion upon stimulation with BMP-2 or BMP-7

Abstract: Fractures to the osteoporotic bone feature a delay in callus formation and reduced enchondral ossification. Human mesenchymal stem cells (hMSC), the cellular source of fracture healing, are recruited to the fracture site by cytokines, such as BMP-2 and BMP-7. Aim of the study was to scrutinize hMSC for osteoporosis associated alterations in BMP mediated migration and invasion as well as in extracellular matrix (ECM) binding integrin expression. HMSC were isolated from 18 healthy or osteoporotic donors. Migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 35 publications
0
31
0
2
Order By: Relevance
“…In such circumstances, the production of bone forming signaling molecules such as TGF-β1 and BMPs are reduced [60] whereas the production of their antagonists is increased [61]. Under such conditions, it is likely that the migration to bone forming surface and the subsequent osteoblastogenesis of MSCs are severely impaired [62,63].…”
Section: How Pathological Conditions Change the Bm?mentioning
confidence: 99%
“…In such circumstances, the production of bone forming signaling molecules such as TGF-β1 and BMPs are reduced [60] whereas the production of their antagonists is increased [61]. Under such conditions, it is likely that the migration to bone forming surface and the subsequent osteoblastogenesis of MSCs are severely impaired [62,63].…”
Section: How Pathological Conditions Change the Bm?mentioning
confidence: 99%
“…BMPs function as both autocrine and paracrine factors, and their synthesis is induced by BMPs themselves via local feedback mechanisms. Evidence has shown that MSCs from osteoporosis patients are impaired in function and this alteration is associated with BMP signaling [95, 96]. However, BMP antagonists have been described, including noggin (NOG) and gremlin (GREM).…”
Section: Introductionmentioning
confidence: 99%
“…12 It has also been demonstrated that MSCs from osteoporotic humans have impaired migration towards chemo-attractants such as foetal calf serum (FCS), bone morphogenetic protein (BMP)-2 and BMP-7 in Boyden chambers, as well as in micro-slide chemotaxis chambers. 13 SDF-1 has previously been shown to recruit more host stem cells to a fracture defect site and to encourage osteogenic differentiation and production of bone. 14 …”
Section: Discussionmentioning
confidence: 99%